dsRNA Binding Domain of PKR Is Proteolytically Released by Enterovirus A71 to Facilitate Viral Replication - Chang, Yu-Hsiu; Lau, Kean Seng; Kuo, Rei-Lin; Horng, Jim-Tong (Frontiers in Cellular and Infection Microbiology, 2017)
Enterovirus 71 (EV-A71) causes hand, foot and mouth disease in young children and infants, but can also cause severe neurological complications or even death. The double-stranded RNA (dsRNA)-dependent protein kinase R (PKR), an interferon-induced antiviral protein, phosphorylates the regulatory -subunit of the eukaryotic translation initiation factor 2 in response to viral infection, thereby blocking the translation of cellular and viral mRNA and promoting apoptosis. The cleavage of PKR after infection with poliovirus, a prototype enterovirus, has been reported by others, but the underlying mechanism of this cleavage and its role in viral replication remain unclear. In the present study, we show that viral 3C protease cleaves PKR at a site, Q188, which differs from the site cleaved during apoptosis, D251. In contrast to the conventional phosphorylation of PKR by dsRNA, EV-A71 3C physically interacts with PKR to mediate the phosphorylation of PKR; this effect is dependent on 3C protease activity. Overexpression of a catalytically inactive PKR mutant (K296H) accelerates viral protein accumulation and increases virus titer, whereas a K64E substitution in the dsRNA binding site abolishes this advantage. We also demonstrate that PKR cleavage mediated by EV-A71 3C protease produces a short N-terminal PKR fragment that can enhance EV-A71 replication, in terms of viral RNA, viral protein, and viral titers. We conclude that PKR is co-opted by EV-A71 via viral protease 3C-mediated proteolytic activation to facilitate viral replication.